Carbon farming in India: are the existing projects inclusive, additional, and permanent? - Adeeth AG Cariappa; Krishna, Vijesh V. (Informa UK Limited, 2025)
As voluntary carbon markets gain popularity, carbon farming emerges as a win-win strategy to mitigate climate change and improve farmers’ income in developing countries. India, with over 50 active carbon farming projects and an impending domestic carbon market, forms an ideal case to explore the early-stage challenges of these initiatives. Using survey data from 841 farmers from seven carbon farming project villages in Haryana and Madhya Pradesh, this study focused on socio-economic inclusion and adherence to additionality and permanence principles, which are underexplored in the existing literature. We found that carbon farmers were predominantly large-holders and from non-marginalized castes, showing patterns of systematic exclusion. Only 4% of participants were women. Around 99% of farmers had not received any monetary benefit. While certain agricultural practices predated carbon projects, raising concerns about additionality, practices like no-tillage, alternate wetting and drying, intercropping, reduced chemical fertilizers, micro-irrigation, and tree planting aligned with additionality principles. Nonetheless, a high disadoption rate (28%) raises concerns about the permanence of emissions reduction. Our findings also indicated that companies that exclusively focus on carbon credits, termed ‘Carbon Core’ companies in this study, were more efficient in spreading regenerative agricultural practices than subsidiaries or offshoots of larger corporations whose primary businesses are unrelated to carbon credits.